Media Accountability in Africa: A Study of Policies and Practices at Two Newsrooms in Kenya. Issue 1 (2nd January 2021) - Obuya, Jared
Abstract: Media accountability has attracted the interest of journalism scholars, media managers and policy makers as the debate grows on how to ensure a free and accountable media. However, media accountability is rarely studied beyond the theoretical and academic debate, especially in many parts of Africa. This article presents the findings of an investigation into media accountability policies and practices at two newsrooms in Kenya. Data came from document analysis and face-to-face interviews with various cadres of journalists and media managers of the newspapers. A range of policies and practices for media accountability guide the journalism at the newsrooms. The editorial policy and other ad hoc policies, routine gate-keeping processes, internal editorial evaluations and capacity-building processes are used to ensure quality and professionalism. The newsrooms also have various practices designed for dialogue and interaction with members of the public. However, media accountability is hampered by a weak professional culture; the dominance of commercial values; and deep ethnic and political fissures in the country. The management of the newsrooms should be encouraged to invest in media accountability as a moral obligation to society and to justify their quest for autonomy and independence from political and economic pressures.